The Bergius Herbarium - Niklas Wikström (GBIF Sweden, 2015)
The Bergius Herbarium is the Bergius Foundations historical collection. It consists mainly of P.J. Bergius own collection with some additions made by the two first Professor Bergiani, O. Swartz and J.E. Wikström. The last accessions were made in 1856. The Bergius Herbarium includes specimens of angiosperms, gymnosperms, algae, bryophytes, fungi and lichens, including some type specimens. Important collectors are C.P. Thunberg, M. Grubb, D. Rolander, P. Osbeck, C.H. Wänman, C.G. Ekeberg, and O. Swartz. There are some 18000 specimens in the Bergius Herbarium, of which about 7200 are included in the dataset.
Keywords: Occurrence; Specimen; Specimen; Type; Historical herbarium; Angiosperms; Occurrence; OCCURRENCE; Biological Sciences; Biologi